2006
DOI: 10.1074/jbc.m509805200
|View full text |Cite
|
Sign up to set email alerts
|

GEC1 Interacts with the κ Opioid Receptor and Enhances Expression of the Receptor

Abstract: We identified a truncated form (38 -117) of GEC1 that interacts with the C-tail of the human opioid receptor (hKOR) by yeast two-hybrid screening. GEC1-(38 -117) did not interact with the C-tail of the or ␦ opioid receptors. GEC1, a 117-amino acid protein (Pellerin, I., Vuillermoz, C., Jouvenot, M., Ordener, C., Royez, M., and Adessi, G. L. (1993) Mol. Cell Endocrinol. 90, R17-R21), is highly homologous to GABARAP, GATE-16, and Apg8/aut7, all members of the microtubule associated protein (MAP) family. In pull-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 53 publications
7
98
0
1
Order By: Relevance
“…Interestingly, some escort proteins are responsible for increasing the cell surface localization of GPCRs by increasing the mature form of the receptors. For example, the glycosylation state of CRLR varies depending on its interaction with different RAMPs (29), GEC1 increases the mature form and the localization of the κ-opioid receptor in the plasma membrane (40), and MRAP2 increases the cell surface presence and maturation of the melanocortin-2 receptor (41). It has also been shown that the pseudosignal peptide of CRF 2α R inhibits the trafficking of the receptor to the plasma membrane by allowing its interaction with calnexin (25,42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some escort proteins are responsible for increasing the cell surface localization of GPCRs by increasing the mature form of the receptors. For example, the glycosylation state of CRLR varies depending on its interaction with different RAMPs (29), GEC1 increases the mature form and the localization of the κ-opioid receptor in the plasma membrane (40), and MRAP2 increases the cell surface presence and maturation of the melanocortin-2 receptor (41). It has also been shown that the pseudosignal peptide of CRF 2α R inhibits the trafficking of the receptor to the plasma membrane by allowing its interaction with calnexin (25,42).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with luciferase siRNA, used as the control, did not affect the hKOPR level compared with no transfection (data not shown). Our previous data showed that FLAG-hKOR migrated as two bands of M r 55 (mature receptor) and 45 (immature receptor) (7). Therefore, 14-3-3 may be involved in regulation of export of hKOPR along the ER-Golgi-plasma membranes in N2A-FLAG-hKOPR cells.…”
Section: Knockdown Of 14-3-3 Decreased Expression Of the Hkopr In N2amentioning
confidence: 99%
“…Experiments were performed using our previously published procedure (7). Cells were washed with DMEM without L-Met and L-Cys and preincubated in the same medium for 1 h at 37°C.…”
Section: S]met/cys Labeling Of the Hkopr And Pulse-chase Experimentsmentioning
confidence: 99%
See 2 more Smart Citations